2021
DOI: 10.1016/j.surg.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Transatlantic registries of pancreatic surgery in the United States of America, Germany, the Netherlands, and Sweden: Comparing design, variables, patients, treatment strategies, and outcomes

Abstract: Background: Registries of pancreatic surgery have become increasingly popular as they facilitate both quality improvement and clinical research. We aimed to compare registries for design, variables collected, patient characteristics, treatment strategies, clinical outcomes, and pathology. Methods: Registered variables and outcomes of pancreatoduodenectomy (2014e2017) in 4 nationwide or multicenter pancreatic surgery registries from the United States of America (American College of Surgeons National Surgical Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 24 publications
(20 reference statements)
2
49
0
Order By: Relevance
“…As concluded in the previous comparison between these 4 registries, implementation of key parameters with identical definitions in the separate registries is required. 8 The Dutch and Swedish registries are nationwide with very high coverage, whereas the NSQIP and German StuDoQ registries are multicenter with a two-third and one-fifth nationwide coverage, respectively. The NQSIP has a high presence of high-volume centers, which could partly explain the high rate of neoadjuvant therapy and improved postoperative outcomes in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As concluded in the previous comparison between these 4 registries, implementation of key parameters with identical definitions in the separate registries is required. 8 The Dutch and Swedish registries are nationwide with very high coverage, whereas the NSQIP and German StuDoQ registries are multicenter with a two-third and one-fifth nationwide coverage, respectively. The NQSIP has a high presence of high-volume centers, which could partly explain the high rate of neoadjuvant therapy and improved postoperative outcomes in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our analyses of patients who underwent PD, Germany had the highest reoperation rate. 8 The high reoperation rate was surprising given the fact that no pancreatic fistula would have been present after surgery, and it is common practice to use a step-up approach before performing a reoperation. Other complications such as postpancreatectomy hemorrhage, bile leak, and organ space surgical site infections are potential indications for reoperation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upfront surgery is still, by far, the most frequently adopted approach for localized pancreatic cancer in both the USA and Europe, even though large retrospective studies ( 3 , 4 ) and a few randomized controlled trials (RCTs) ( 5 , 6 ) have observed prognostic improvements with neoadjuvant treatments. A recent paper analyzing national registries in the USA and in some European countries demonstrated that from 2014 to 2017, the rate of pancreatic cancer patients receiving preoperative chemotherapy was 27.6% in the USA, 4.9% in Germany, 7.0% in the Netherlands, and 3.4% in Sweden ( 7 ).…”
Section: Introductionmentioning
confidence: 99%